Rare complex recurrent cystic echinococcosis with multi-organ involvement after inadequate postoperative therapy: a case report - Zhong, Yue; Yuan, You; Zhang, Yuting; Zheng, Yu; Chen, Chunyan (Frontiers in Medicine, 2025)
BackgroundCystic echinococcosis (CE) is a globally prevalent zoonotic parasitic disease. Multi-organ recurrent CE is extremely rare, particularly in patients lacking standardized postoperative antiparasitic therapy or regular follow-up.Case presentationWe report a 29-year-old Tibetan male who presented with progressive abdominal pain, distension, and a 15-kg weight loss over 6 months. He had undergone hepatic CE cystectomy 5 years earlier but did not receive regular albendazole therapy or follow-up. Imaging revealed multiple cystic lesions in the liver, spleen, greater omentum, and pelvic cavity. More than 13 lesions, including hepatic and diaphragmatic lesions, were excised during surgery, with concurrent management of vascular and urinary tract involvement. Intraoperative blood loss was approximately 2,800 mL, which required transfusion support and intensive care monitoring.ResultsThe patient stayed in the intensive care unit for 7 days and spent a total of 46 days in the hospital. After surgery, albendazole therapy was resumed. Follow-up evaluations at 1, 6, and 12 months showed no signs of recurrence, and long-term follow-up is still ongoing. Due to the potential for late recurrence of cystic echinococcosis, continued long-term monitoring is recommended.ConclusionManagement of multi-organ recurrent CE requires standardized surgery, multidisciplinary collaboration, prolonged antiparasitic therapy, and strict follow-up. Ensuring patient adherence and providing health education are critical for improving long-term outcomes.